Could Dietary Goals and Climate Change Mitigation Be Achieved Through Optimized Diet? The Experience of Modeling the National Food Consumption Data in Italy - Ferrari, Marika; Benvenuti, Luca; Rossi, Laura; De Santis, Alberto; Sette, Stefania; Martone, Deborah; Piccinelli, Raffaela; Le Donne, Cinzia; Leclercq, Catherine; Turrini, Aida (Frontiers in Nutrition, 2020)
Objective The aim of this study is to define a healthy and sustainable diet model with low GHGE, fulfilling dietary requirements, and considering current Italian food consumption patterns. Design A duly designed database was developed, linking food nutritional composition and GHGE based on 921 foods items consumed in Italy according to the last national food consumption survey (INRAN-SCAI 2005-2006). Linear programming was used to develop new diet plans separately for males and females, aged 18-60 years (n=2,098 subjects), in order to minimize GHGE. The program is based on dietary goals and acceptability constraints as well as on 13 nutrient requirement constraints aiming to reach a healthy and acceptable diet for the Italian population. Results Diet optimization resulted in a nutritionally adequate pattern minimizing GHGE values (4.0 versus 1.9 Kg CO2e/day for males and 3.2 versus 1.6 Kg CO2e/day for females). In both sexes, the nutrient intake of the optimized diet was at established lower bound for cholesterol and calcium and at established upper bound for free sugar and fiber. In males, intake of zinc was at established lower bound whereas iron was at established upper bound. Consumption of read meat and fruit and vegetables were at established lower and upper bound respectively in both males and females. Despite the decrease in meat consumption, especially red meat, in the optimized diet respect to the observed diet, levels of iron intake in females increased by 10% (10.3 mg/day versus 11.3 mg/day) but remained below the adequate intake established in Italian national DRIs. Conclusions An attainable healthy dietary pattern was developed that would lead to the reduction of GHGE by 48% for males and by 50% for females with respect to current food consumption in the Italian adult population. Health-promoting dietary patterns can substantially contribute to achieve related Sustainable Development Goals.